Comparação da resposta inflamatória sistêmica entre dieta mediterrânea e exercício físico no curto prazo em mulheres com índice de massa corporal igual ou superior a 25kg/m2 na pós menopausa: estudo piloto comparativo - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Menopause is a natural biological process that marks the end of women's menstrual periods. During this period, hormonal changes can lead to a variety of symptoms, including hot flashes, mood swings and weight gain. Obesity is a condition characterized by excess adipose tissue, which can increase the risk of several diseases, including cardiovascular disease, diabetes and certain types of cancer. Research suggests that estrogen has a role in regulating C-reactive protein, and the decline in estrogen during menopause leads to its decline. Regular physical exercise and adequate nutrition can be important tools for weight loss and likely instruments for reducing the increase in serum concentration of C-reactive Protein. The study “Comparison of the systemic inflammatory response between Mediterranean diet and physical exercise at short term in postmenopausal women with a body mass index equal to or greater than 25kg/m2: Comparative pilot study” has as its main study objective the analysis and comparison of plasma concentrations of C-reactive protein (CRP) and anthropometric measurements. weight, height, body mass index (BMI), waist circumference (WC), hip circumference (HC), waist-to-hip ratio (WHR) in postmenopausal women with a BMI equal to or greater than 25kg/m2, before and after interventions with physical exercise and diet, aiming to determine the real weight that each factor exerts on chronic systemic inflammation. 30 sedentary postmenopausal women with overweight/obesity (BMI>25kg/m2) were selected and were randomly assigned and divided into 2 groups. The first group underwent a qualitative dietary intervention (without the need to weigh and measure food), based on the Mediterranean Diet. The second group participated in CrossFit classes, performing 3 sessions on alternate days of the week (Monday, Wednesday and Friday), totaling 3 hours/week. The results of the present study demonstrated that, despite the numerical differences, in both interventions, there was a reduction in CRP concentrations and anthropometric measurements when comparing pre and post intervention. Despite the visible numerical reduction in the variables analyzed, due to the limitations of the work, we see that more studies in the area are necessary. It was concluded that both interventions, with physical exercise and diet, as isolated factors, were effective in reducing circulating CRP levels.
Keywords: Exercício físico; Nutrição; Inflamação; Physical exercise; Nutrition; Inflammation; CNPQ::CIENCIAS DA SAUDE